2021
DOI: 10.7759/cureus.20460
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Subacute Transverse Myelitis Following Vaccination With Pfizer-BioNTech COVID-19 mRNA Vaccine: A Case Report

Abstract: In response to the coronavirus disease 2019 (COVID-19) pandemic, rapid development, clinical testing, and regulatory approval of vaccines occurred. The tozinameran COVID-19 vaccine is the first mRNA vaccine approved for use in humans. Transverse myelitis is a rare inflammatory disorder of the spinal cord that is associated with traditional vaccinations. There are rare case reports describing an association between mRNA vaccines and transverse myelitis. Herein, we describe a case of transverse myelitis followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Out of 11 ADEM ( 41 49 ), six occurred after an adenoviral-vectored (55%), three after an mRNA-based (27%), and two after an inactivated vaccine (18%; Figure 4A ). The median time from vaccine to symptoms onset was 12.5 days ( 2 30 ) ( Figure 4D ), with all but one case occurring at least after 7 days. Median age was 46 years and the female sex was prevalent (73%; Figures 4B , C ).…”
Section: Resultsmentioning
confidence: 99%
“…Out of 11 ADEM ( 41 49 ), six occurred after an adenoviral-vectored (55%), three after an mRNA-based (27%), and two after an inactivated vaccine (18%; Figure 4A ). The median time from vaccine to symptoms onset was 12.5 days ( 2 30 ) ( Figure 4D ), with all but one case occurring at least after 7 days. Median age was 46 years and the female sex was prevalent (73%; Figures 4B , C ).…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA flowchart ( Figure 1 ) showed a search strategy for our review. The present study consisted of 28 studies, including 26 case reports, one case series, and one cross-sectional, and the pooled data of 31 patients with COVID-19 vaccine-associated ATM is extracted ( Sriwastava et al, 2021 , Sepahvand et al, 2022 , Tan et al, 2021 , Corrêa et al, 2021 , Vegezzi et al, 2021 , Hsiao et al, 2021 , Pagenkopf and Südmeyer, 2021 , Notghi et al, 2021 , Gao et al, 2021 , Malhotra et al, 2021 , Khan et al, 2022 , Erdem et al, 2021 , Hirose et al, 2021 , Tahir et al, 2021 , Miyaue et al, 2021 , Fujikawa et al, 2021 , Kaulen et al, 2022 , McLean and Trefts, 2021 , Alabkal et al, 2021 , Fitzsimmons and Nance, 2021 , Nakano et al, 2022 , Spataro et al, 2022 , Cabral et al, 2022 , Khan et al, 2022 , Maroufi et al, 2022 , Eom et al, 2022 , Netravathi et al, 2022 , Esechie et al, 2022 ). All of the selected studies were written in the English language.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was not possible to conclude on the causal link between the two events since the subject in question was under long-term treatment with a TNF-a inhibitor for rheumatoid arthritis, which has been associated with an increased risk of demyelinating diseases 29 . Despite this, rare cases of transverse myelitis after the Pfizer-BioNTech COVID-19 vaccine have been described in the literature [30][31][32][33] . A case of sudden hearing loss was also observed; however, studies have shown that there is no clear association between this adverse reaction and the administration of vaccines against COVID-19 34 .…”
Section: Discussionmentioning
confidence: 99%